Paediatric allergy; what do our patients really think?. (24th May 2012) - Rothenberg, TM; O'Keeffe, C; Henley, F; Morales, F; Leitiano, E; Warner, JO
Abstract : Background: Patient reported experience measures (PREMs) are a useful tool to measure quality and improve standards. Method: Two PREMs were developed for children and young adults with allergic disease. Survey 1, "Your child's allergy care" was distributed to the parents of children aged under 8 years. Survey 2, "your allergy care", was distributed to patients aged 8 years and over, with a set of questions asked directly to those children and young adults, and questions directed at the patient's parent/carer. This survey was offered over a period of two months (December 2010 to January 2011) to all patients attending outpatient and daycase services at a tertiary paediatric allergy unit in the UK. Results: 106 surveys were returned, (60 from Survey 1 and 40 from survey 2). Gender, age and ethnicity were representative of the general population. 50% of surveys were filled in predominantly by the patient, or patient and carer together. The proportion of respondents rating the overall care for their own or their child's allergy care as good or excellent was 0.74, and poor or fair was 0.04. The proportion describing communication between health care professionals as not very good or not at all good was 0.34, which increased to 0.5 when describing that between health care professionals and school/nursery. The proportion of respondents wanting more information on an aspect of their care was 0.73, (0.42 wanted more information on long term health effects, 0.26 more information on choice of medicines and creams). No respondent felt there they had been given too much information on preventing the condition getting worse. Conclusion: Parents and patients are concerned about long term health effects. While patients may be relatively satisfied with services provided in a tertiary centre, there are great improvements to be made in communication between health care providers and between health and school/nursery.